Assessing international scientific cooperation in the Mediterranean region. An international challenge ahead - Arvanitis R.; Atweh R.; M'Henni H. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
The article is based on the White paper that was elaborated by the Observatory of Scientific Cooperation in the Mediterranean. It examines the theoretical and institutional background, then proposes a series of indicators and initiatives that can be taken in the future. The article shows the possible relation between the policy objectives of the Cairo Declaration and the indicators needed. It also examines the needs for the creation of a more permanent Observatory in the region.